Legislative voting and accountability - Carey, John M. (Cambridge studies in comparative politics, 2009)
Legislatures are the core representative institutions in modern democracies. Citizens want legislatures to be decisive, and they want accountability, but they are frequently disillusioned with the representation legislators deliver. Political parties can provide decisiveness in legislatures, and they may provide collective accountability, but citizens and political reformers frequently demand another type of accountability from legislators – at the individual level. Can legislatures provide both kinds of accountability? This book considers what collective and individual accountability require and provides the most extensive cross-national analysis of legislative voting undertaken to date. It illustrates the balance between individualistic and collective representation in democracies, and how party unity in legislative voting shapes that balance. In addition to quantitative analysis of voting patterns, the book draws on extensive field and archival research to provide an extensive assessment of legislative transparency throughout the Americas